Application The Adaptive Inquiry Based Learning Model Assisted by PhET Media in Improving Understanding Of Light Concepts - Siti Hana M. Saboy; Muh. Khaerul Ummah BK; Saaskia Amalia; Ela Anipratiwi A. Udit (Horizon of Primary Education, 2025)
This study aims to test the effectiveness of the application of the Adaptive Inquiry-Based Learning model in science learning in elementary schools. The background of the research raises the problem of low student learning outcomes in abstract light materials. The researcher applied a quasi-experimental method with the Nonequivalent Control Group Design during the research process. The research subjects included 30 grade IV students of SDN Oyom who were divided into two parallel classes. The test instrument collects concept comprehension data through 20 valid and reliable multiple-choice questions. The results of the study showed a significant increase in the experimental class. Students of the experimental class achieved an N-Gain score of 0.91 in the high category. In contrast, students in the control class obtained an N-Gain score of 0.60 in the medium category. The t-test proves a noticeable difference between the two groups. In conclusion, the Adaptive Inquiry-Based Learning model effectively improves the understanding of light concepts through the help of PhET Media.